Multiplatform Anti Perundungan Sebagai Strategi Mewujudkan Madrasah Inklusi Dan Ramah Anak Di Man Banyuwangi - Farras, Muhaammad Taqy Al; Hadi, Muhamaad Samsul; Fitriana, Ani Qotuz Zuhro’ (CV. ITTC INDONESIA, 2023)
Problems in the world of education will continue to exist and always demand the attention of all people and the world. This is because educational institutions are the basis and foundation in preparing the next generation. Education is the backbone of success in creating a glorious generation. Therefore education should be enjoyed by all students. The term that can represent this understanding is education for all or is inclusive. This type of research is a literature study. The literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. This research will present five platforms for the anti-bullying movement that can be implemented in madrasas or schools. The presentations include (1) Empathy Skills Training Program with